JENIS DAN KEPADATAN FITOPLANKTON PADA KEDALAMAN BERBEDA DI LOKASI BUDIDAYA KERANG MUTIARA DI BALAI PERIKANAN BUDIDAYA LAUT LOMBOK - Sombak, Nurnamsi Masrik; Linggi, Yulianus; Santoso, Priyo (Nusa Cendana University, 2025)
This study aims to identify the types and densities of phytoplankton at different depths in the pearl oyster (Pinctada maxima) aquaculture area at the Marine Aquaculture Center, Lombok. The research was conducted from August to October 2024. Water samples were collected from three stations at three depth points: surface, near the pocket, and bottom. A total of 38 genera from 10 phytoplankton classes were identified, with Bacillariophyceae being the most dominant. The highest density was found at the bottom of Station 2 (3400 ind/L), indicating nutrient accumulation. Depth significantly affected phytoplankton distribution more than spatial location. These results provide ecological information supporting sustainable aquaculture. Keywords: Bacillariophyceae, phytoplankton, depth, density, pearl oysters.